Peningkatan Pelayanan Wisatawan dengan Penyusunan SOP Wisata Kampung Pecinan di Kelurahan Kapasan, Kota Surabaya - Heidy Arviani; Vembika Fathan Kusuma; Via Rahma Aulinda; Uswatul Husna (Jurnal Gema Ngabdi, 2022)
Standard Operating Procedures (SOP) is a standard in activities that coherently complete a job. One of the activities that require the establishment of SOPs is the management of tourist sites, one of which is the management of Wisata Kampung Pecinan (WKP), located in Kapasan Village, Simokerto District, Surabaya City. WKP is a tourist attraction that has been running for approximately 1.5 years, and many tourists have visited. However, WKP still does not have an SOP regulating all its activities, so it affects the quality of service and management of tourist attractions to be less than optimal. Therefore, in WKP management, it is necessary to prepare an SOP that regulates all activities. With the hope that it can become a guideline and consideration in implementing WKP management in the future. Making this SOP aims to improve the quality of Kampung Pecinan services and a form of community service. The preparation of the SOP consists of 4 stages of activities, including 1. The survey, 2. Discussion, 3. Preparation of SOP, and 4. Socialization. After going through these stages, they produce SOPs expected to improve the quality of service from WKP